Integral Humanism: Theoretical Issues and Challenges for Practice - Sah, Mukesh Kumar (NPRC Journal of Multidisciplinary Research, 2024)
Integral Humanism (IH), propounded by great Indian philosopher Deendayal Upadhyaya, opposes the materialistic and collectivist policies economically, socially and spiritually. This type of philosophy must be understood as a concept as the enhancement of the value of the person as well as the common good of every social subject. This present paper assess the epistemological perspectives which form the basis of IH and the practical performance difficulties of the outlook in contemporary socio political landscapes. By developing theoretical proposition, it is established that, despite the fact IH encompasses a plurality of options to standard ideologies to the practice of which numerous difficulties arise due to the complications of the contemporary governance, various types of the economies, and cultural diversities. At the end of the study, conclusions followed by recommended solutions and added research directions for minimizing the gap between the theory and practice.